Estimation of influence channels' condition for relative speed of information interchange - Бабак, В.П.; Василенко, В.С.; Юдін, О.К. (Proceedings of National Aviation University (archive), 2005)
The analysis of dependence of relative speed from a condition of channels for the protocols of information interchange in telecommunication systems was offered, given expressions for his accounts is.